Teriparatide for Patients with RA and Osteoporosis Requires More Study - Lederman, Lynne (MD Conference Express, 2014)
Early intensive treatment with methotrexate (MTX) and biologic agents is effective in rheumatoid arthritis (RA), but comorbidities, such as osteoporosis, also require treatment to reduce morbidity and improve quality of life. One treatment is daily teriparatide [European League Against Rheumatism 2014 (abstract OPO276)]. Osteoporosis in patients with RA is multifactorial; excess inflammatory cytokines, corticosteroids used to treat the disease, decreased activity due to joint pain, and postmenopausal osteoporosis are contributory factors.